2019
DOI: 10.1111/joim.12871
|View full text |Cite
|
Sign up to set email alerts
|

Novel mediators and mechanisms in the resolution of infectious inflammation: evidence for vagus regulation

Abstract: Excessive chronic inflammation is linked to many diseases and considered a stress factor in humans (Robbins Pathologic Basis of Disease. Philadelphia: W.B. Saunders Co., 1999, Proc Natl Acad Sci USA, 2008, 105: 17949, Immunity, 44, 2016, 44: 463, N Engl J Med, 2011, 364: 656). Today, the resolution of inflammation is widely recognized as a cellular biochemically active process involving biosynthesis of a novel superfamily of endogenous chemical signals coined specialized pro‐resolving mediators (SPMs; Nature, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
47
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 169 publications
(282 reference statements)
3
47
0
Order By: Relevance
“…Specialized pro-resolving mediators (SPMs) known as lipoxins, resolvins, protectins, and maresins are potent enzymatically-derived metabolites that orchestrate the resolution phase of inflammation and regeneration of damaged tissues [1][2][3][4] . SPMs are synthesized predominately from the n-3 polyunsaturated fatty acids (PUFAs) eicosapentaenoic (EPA) and docosahexaenoic acid (DHA) 1 .…”
Section: Introductionmentioning
confidence: 99%
“…Specialized pro-resolving mediators (SPMs) known as lipoxins, resolvins, protectins, and maresins are potent enzymatically-derived metabolites that orchestrate the resolution phase of inflammation and regeneration of damaged tissues [1][2][3][4] . SPMs are synthesized predominately from the n-3 polyunsaturated fatty acids (PUFAs) eicosapentaenoic (EPA) and docosahexaenoic acid (DHA) 1 .…”
Section: Introductionmentioning
confidence: 99%
“…It was demonstrated that PCTR1 is increased to enhance macrophage recruitment and phagocytosis during the in ammation resolution phase [12] . Moreover, PCTR1 generation in peritoneal lavage is decreased in vagotomized mice, suggesting that PCTR1 is controlled by local vagal to improve in ammation resolution [13] . Our previous studies demonstrated that PCTR1 reduced LPS-induced in ammation in mice via regulating linoleic acid metabolism, and improved pulmonary edema uid clearance by activating the sodium channel and lymphatic drainage in LPS-triggered rat model [17,18] .…”
Section: Discussionmentioning
confidence: 99%
“…PCTR1 is identi ed and present in vivo before infection, and increases after LPS-induced in ammation, especially in in ammation resolution phrase [12] . Notably, PCTR1 not only enhances in ammation resolution by promoting macrophage efferocytosis and phagocytosis in infectious disease models but also improves tissue reparation [13,14] . However, the effect of PCTR1 on endothelial glycocalyx is still unde ned.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, Seheran et al . provided evidence that signals via the vagus nerve regulate resolution of inflammation . The findings suggest that it may be possible to target the vagus nerve to accelerate resolution of inflammation and raises the question whether other nerves can be activated therapeutically to release pro‐resolving mediators and promote resolution of inflammation and tissue repair.…”
mentioning
confidence: 99%
“…Disruption of signalling in the vagus nerve by vagotomy delayed resolution of peritonitis and bacterial infection in mice, and acetylcholine, a vagus nerve neurotransmitter, promoted biosynthesis of pro-resolving mediators. Indeed, Seheran et al provided evidence that signals via the vagus nerve regulate resolution of inflammation [9]. The findings suggest that it may be possible to target the vagus nerve to accelerate resolution of inflammation and raises the question whether other nerves can be activated therapeutically to release pro-resolving mediators and promote resolution of inflammation and tissue repair.…”
mentioning
confidence: 99%